Physico-chemical factors influencing the spatial and temporal distribution of the seagrass Zostera capensis in Langebaan lagoon - Arendse, Brittany (Department of Biological Sciences, 2017)
Seagrass meadows have important ecological roles in coastal ecosystems and provide high-value ecosystems services compared to other marine and terrestrial habitats. Despite this, there is growing evidence that this key ecosystems is declining on a global scale. Much of these declines have been attributed to the effects of human alterations of marine habitats. Continued destructive activities, in both South Africa and elsewhere, if not managed properly will result in the demise of seagrass beds from coastal areas. With this in mind, the aim of the project is to determine the main physico-chemical factors influencing Zostera capensis biomass and distribution in Langebaan Lagoon. Five sites within the Langebaan Lagoon were selected and within these sites a minimum of three and maximum of ten Z. capensis beds were sampled, depending on the availability of the beds. Five 10 cm core samples were collected from each bed, from which seagrass biomass, density, leaf length, leaf width and epiphytic algal biomass were estimated. Physico-chemical data were collected with a CTD to test for the differences in: temperature, turbidity, pH, salinity, dissolved oxygen and dissolved chlorophyll levels. The results indicated that temperature and salinity are the main factors driving biomass and distribution along Langebaan Lagoon. Increasing temperature appears to have a negative effect on both leaf length and leaf width, while increasing salinity has a positive effect on seagrass biomass. Although, the ancestral seagrass populations thrived in conditions of higher temperatures, today the rates of change along the coast is so rapid that seagrass populations cannot keep up with this change. In addition, sites near the open ocean experienced a higher seagrass biomass than the sites further away, indicating that salinity is an important factor driving growth and distribution. However, temperature and salinity are not the sole factor responsible for the distribution of Z. capensis at Langebaan lagoon. Turbidity and dissolved chlorophyll also appear to impact certain sites more than others. It is thus clear that at least a few other factors must be considered: the interaction between nutrients, epiphytes and macrograzers and the plants tolerance to the sediment quality. These different aspects need to be studied in concert in order to perceive the full range of impacts on the Z. capensis beds and to better manage these ever-declining key ecosystems.